Higher education financing in Japan: Trends and challenges. (January 2018) - Huang, Futao
Abstract: The purpose of this study is to address the basic model of Japanese higher education financing mechanisms, the main changes that have occurred in these mechanisms, and their influences on higher education development. This analysis is based on previous academic studies, national statistics, and case studies of three different sectors since the early 2000s. The analysis begins with a brief review of earlier studies and a description of the research framework. Subsequently, the study outlines the main characteristics of Japan's higher education and the key features of its financing mechanisms. In the following part, the study analyzes major changes that have occurred in Japanese higher education financing in recent years, and key factors that have affected these changes. Furthermore, it discusses the major influences and outcomes of these financing mechanisms on higher education development and institutional strategies. The final part summarizes and offers implications for research, practice and educational development.